EFEKTIVITAS COGNITIVE BEHAVIOR THERAPY UNTUK MENINGKATKAN PERSONAL BRANDING PADA REMAJA - Nabil Amiroh Bilqis; Abdul Muhid (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2021)
Currently the development of technology causes the development of community communication patterns with the media in the community. Social media is often used to brand or promote the products they sell. In addition to promoting products, many people also carry out personal branding activities. This personal branding activity is often found among teenagers. However, in doing personal branding, many teenagers experience a lack of self-confidence, feel inferior and close themselves off. For this reason, the strategy used to improve personal branding in adolescents is through cognitive behavior therapy. The purpose of this study was to determine the effectiveness of cognitive behavior therapy in improving personal branding in adolescents. This study uses a qualitative method with a literature review approach as the research method. The results of the study indicate that cognitive behavior therapy can be used to improve personal branding in adolescents.